Measurement of the forward-backward asymmetry in top quark-antiquark production in p(p)over-bar collisions using the lepton plus jets channel - Abazov,VM; Abbott,B; Acharya,BS; Adams,M; Adams,T; Agnew,JP; Alexeev,GD; Alkhazov,G; Alton,A; Askew,A; Atkins,S; Augsten,K; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2014)
We present a measurement of the forward–backward asymmetry in top quark–antiquark production using the full Tevatron Run II data set collected by the D0 experiment at Fermilab. The measurement is performed in lepton+jets final states using a new kinematic fitting algorithm for events with four or more jets and a new partial reconstruction algorithm for events with only three jets. Corrected for detector acceptance and resolution effects, the asymmetry is evaluated to be AFB=(10.6±3.0)%. Results are consistent with the standard model predictions which range from 5.0% to 8.8%. We also present the dependence of the asymmetry on the invariant mass of the top quark–antiquark system and the difference in rapidities of the top quark and antiquark.